Rapid and Sensitive Detection of Thrombospondin-2 Using Nanoparticle Sensors for Cancer Screening and Prognosis - Maziyar Kalateh Mohammadi; Seyedsina Mirjalili; Md Ashif Ikbal; Hao Xie; Chao Wang (Micromachines)
Thrombospondin-2 (THBS2) is a prevailing prognostic biomarker implicated in different cancer types, such as deadly colorectal, pancreas, and triple-negative breast cancers. While the current methods for cancer-relevant protein detection, such as enzyme-linked immunosorbent assay (ELISA), mass spectrometry, and immunohistochemistry, are feasible at advanced stages, they have shortcomings in sensitivity, specificity, and accessibility, particularly at low concentrations in complex biological fluids for early detection. Here, we propose and demonstrate a modular, in-solution assay design concept, Nanoparticle-Supported Rapid Electronic Detection (NasRED), as a versatile cancer screening and diagnostic platform. NasRED utilizes antibody-functionalized gold nanoparticles (AuNPs) to capture target proteins from a minute amount of sample (<10 µL) and achieve optimal performance with a short assay time by introducing active fluidic forces that act to promote biochemical reaction and accelerate signal transduction. This rapid (15 min) process serves to form AuNP clusters upon THBS2 binding and subsequently precipitate such clusters, resulting in color modulation of the test tubes that is dependent on the THBS2 concentration. Finally, a semiconductor-based, portable electronic device is used to digitize the optical signals for the sensitive detection of THBS2. High sensitivity (femtomolar level) and a large dynamic range (five orders of magnitude) are obtained to analyze THBS2 spiked in PBS, serum, whole blood, saliva, cerebrospinal fluids, and synovial fluids. High specificity is also preserved in differentiating THBS2 from other markers such as cancer antigen (CA) 19-9 and bovine serum albumin (BSA). This study highlights NasRED’s potential to enhance cancer prognosis and screening by offering a cost-effective, accessible, and minimally invasive solution.